2012
DOI: 10.1007/s11325-012-0702-6
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of continuous positive airway pressure adherence in a sleep clinic cohort of South Florida Hispanic veterans

Abstract: Our study suggests that South Florida Hispanic veterans with OSA evaluated in a sleep clinic show poor CPAP adherence. Insomnia and poor early use predicted poor adherence overall. Larger prospective studies with other race-ethnic groups are needed to determine the role of ethnicity and race in CPAP adherence among US veterans with OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 53 publications
7
49
1
Order By: Relevance
“…Timing is an important factor that can increase patient motivation, since the first days of treatment are key to increasing adherence [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Timing is an important factor that can increase patient motivation, since the first days of treatment are key to increasing adherence [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the previous studies did not control for confounders, such as OSA symptoms (e.g., daytime sleepiness), comorbid conditions of OSA and depression (e.g., insomnia and anxiety), or use and compliance with antidepressant medications which may influence CPAP adherence. Studies have also suggested that race and ethnicity may influence CPAP adherence in OSA patients [63,64]. Furthermore, mental disorders may interact with ethnicity to influence CPAP acceptance and adherence.…”
Section: Relationship Between Depression and Cpap Adherencementioning
confidence: 99%
“…One study of a public healthcare system in southern California found that Hispanics may be less accepting of CPAP home set up compared to whites. 111 Once set up with CPAP, data are conflicting on whether adherence rates in Hispanics are similar or worse than whites 103,109,112 A possible explanation for poorer CPAP adherence in Hispanics may be poor communication with healthcare providers due to language barriers. In one study, only about half of Hispanics reported that their sleep study results had been explained to them in their language.…”
Section: Introductionmentioning
confidence: 99%